Living and dying with advanced dementia: A prospective cohort study of symptoms, service use and care at the end of life. (March 2018) - Sampson, Elizabeth L; Candy, Bridget; Davis, Sarah; Gola, Anna Buylova; Harrington, Jane; King, Michael; Kupeli, Nuriye; Leavey, Gerry; Moore, Kirsten; Nazareth, Irwin; Omar, Rumana Z; Vickerstaff, Victoria; et al.
Background: Increasing number of people are dying with advanced dementia. Comfort and quality of life are key goals of care. Aims: To describe (1) physical and psychological symptoms, (2) health and social care service utilisation and (3) care at end of life in people with advanced dementia. Design: 9-month prospective cohort study. Setting and participants: Greater London, England, people with advanced dementia (Functional Assessment Staging Scale 6e and above) from 14 nursing homes or their own homes. Main outcome measures: At study entry and monthly: prescriptions, Charlson Comorbidity Index, pressure sore risk/severity (Waterlow Scale/Stirling Scale, respectively), acute medical events, pain (Pain Assessment in Advanced Dementia), neuropsychiatric symptoms (Neuropsychiatric Inventory), quality of life (Quality of Life in Late-Stage Dementia Scale), resource use (Resource Utilization in Dementia Questionnaire and Client Services Receipt Inventory), presence/type of advance care plans, interventions, mortality, place of death and comfort (Symptom Management at End of Life in Dementia Scale). Results: Of 159 potential participants, 85 were recruited (62% alive at end of follow-up). Pain (11% at rest, 61% on movement) and significant agitation (54%) were common and persistent. Aspiration, dyspnoea, septicaemia and pneumonia were more frequent in those who died. In total, 76% had 'do not resuscitate' statements, less than 40% advance care plans. Most received primary care visits, there was little input from geriatrics or mental health but contact with emergency paramedics was common. Conclusion: People with advanced dementia lived with distressing symptoms. Service provision was not tailored to their needs. Longitudinal multidisciplinary input could optimise symptom control and quality of life.